2023
DOI: 10.1177/09603271231155098
|View full text |Cite
|
Sign up to set email alerts
|

Irigenin attenuates lipopolysaccharide-induced acute lung injury by inactivating the mitogen-activated protein kinase (MAPK) signaling pathway

Abstract: Acute lung injury (ALI) is a serious pulmonary inflammation disease with high mortality. Irigenin, an isoflavone from rhizomes of the Belamcanda chinensis, has been reported to exert anti-inflammatory, anti-oxidative, and anti-apoptotic activities in several diseases. However, it is still unclear whether irigenin can exert a beneficial effect in ALI. A network pharmacology method was utilized to predict the hub targets and potential therapeutic mechanisms of irigenin against ALI. Lipopolysaccharide (LPS) was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The protein target MAPK1 (ERK2), known for its regulation of inflammatory responses, cellular apoptosis, and lipid metabolism, was reported to participate in the occurrence and progression of ALI (Liu et al, 2023; Zhang et al, 2023). Naringenin was shown to alleviate inflammation, apoptosis, and ferroptosis associated with lung injury (Zhang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The protein target MAPK1 (ERK2), known for its regulation of inflammatory responses, cellular apoptosis, and lipid metabolism, was reported to participate in the occurrence and progression of ALI (Liu et al, 2023; Zhang et al, 2023). Naringenin was shown to alleviate inflammation, apoptosis, and ferroptosis associated with lung injury (Zhang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the MAPK/Erk signaling pathway is implicated in the progression of diverse lung ailments. For instance, irigenin was observed to mitigate LPS-induced lung injury through the inhibition of lung cell apoptosis by restraining the MAPK/Erk signaling pathway 47 . In our study, treadmill training exhibited the ability to suppress the expression of MAP3K3 and p-Erk, resulting in reduced expression of pro-apoptotic factors such as Bax, CytC, caspase 3, and caspase 9, coupled with upregulated expression of the anti-apoptotic factor Bcl-2 within lung tissues of SCI rats.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of MAPK signaling is also demonstrated to contribute to the anti-inflammatory effects in ARDS treatment. Nicotinamide [ 101 ], Irigenin [ 259 ] and β-Caryophyllene [ 260 ] have been recently found to inhibit MAPK signaling and reduce expression of inflammatory factors in ALI model. Particularly, Dilmapimod, a specific p38MAPK inhibitor, has been reported to have a satisfactory safety profile in trauma patients at risk of developing ARDS and to reduce the concentration of pro-inflammatory cytokines [ 261 ].…”
Section: Emerging Pharmacologic Therapies For Ardsmentioning
confidence: 99%